Pengaruh Latihan Kekuatan dan Latihan Keseimbangan terhadap Kebugaran Fisik, Kesehatan Mental, dan Kesejahteraan Sosial Atlet Para-Judo: Sebuah Studi Eksperimental - Dyah Sukma Ramadhani; Abdul Rahman Syam Tuasikal; Nanik Indahwati (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aimed to analyze the effects of strength and balance training on physical fitness, mental health, and social well-being among male para-judo athletes affiliated with the National Paralympic Committee Indonesia (NPCI). A quantitative research design employing a one-group pretest–posttest model was used. Ten male para-judo athletes (J1 = 6, J2 = 4; age range 20–29 years) participated in an eight-week structured program. Instruments included physical fitness tests (grip strength, bench press, deadlift, sit-up, back-up), balance assessment (standing stroke test blind), and psychological evaluation using the WHO-5 Well-Being Index and social welfare scale. Data were analyzed using paired t-tests with a significance level of p < 0.05. Findings revealed significant improvements across all physical variables (p < 0.01), including grip strength, deadlift, and sit-up performance. Mental well-being scores increased significantly (mean difference = 3.5, p = 0.002), as did social welfare (mean difference = 4.2, p = 0.004). The effect size (Cohen’s d = 0.81) indicated a strong influence of the combined strength and balance training on all three domains. An eight-week integrated strength and balance training program significantly enhanced the physical fitness, mental well-being, and social welfare of visually impaired para-judo athletes. These findings underscore the importance of a holistic and evidence-based training framework for promoting both performance and quality of life among athletes with disabilities. Keywords: Para-judo, strength training, balance training, mental health, social well-being, disabled athletes